2018
DOI: 10.1002/psp.2221
|View full text |Cite
|
Sign up to set email alerts
|

“Kites” and “anchors”: The (im)mobility strategies of transnational Latin American families against the crisis in Spain

Abstract: The impact of the recent global financial and economic crisis on migration to Spain has generated literature focusing mainly on demographic and labour impacts. Internationally, economic crises have also been linked to the increased vulnerability of migrants and return migration. However, this article reveals a more complex picture of how the crisis is producing new (im)mobilities between Latin America and Europe.It adopts a transnational family approach based on qualitative fieldwork with Colombian, Ecuadorean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Although these new moves are mostly a result of a specific event, the 2008 economic crisis, they should be understood within a broader context in which multiple moves are common. A growing body of research in the EU examines the mobility practices of those who engage in onward or circular migration between one or more member states for a variety of reasons, such as disappointing job opportunities, discrimination, precariousness and changing economic contexts (Ahrens et al, 2016; Della Puppa and Sredanovic, 2016; McIlwaine and Bunge, 2016; Schrooten et al 2016; Mas Giralt, 2017; Moret, 2018; Ortensi and Barbiano di Belgiojoso, 2018; Oso and Bermudez 2018). In addition, onward migration seems to be an important strategy among those who have become European citizens and can mobilize their European citizenship to try to escape economic hardship in the host country (Della Puppa and Sredanovic, 2016; McIlwaine and Bunge 2016; Ramos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although these new moves are mostly a result of a specific event, the 2008 economic crisis, they should be understood within a broader context in which multiple moves are common. A growing body of research in the EU examines the mobility practices of those who engage in onward or circular migration between one or more member states for a variety of reasons, such as disappointing job opportunities, discrimination, precariousness and changing economic contexts (Ahrens et al, 2016; Della Puppa and Sredanovic, 2016; McIlwaine and Bunge, 2016; Schrooten et al 2016; Mas Giralt, 2017; Moret, 2018; Ortensi and Barbiano di Belgiojoso, 2018; Oso and Bermudez 2018). In addition, onward migration seems to be an important strategy among those who have become European citizens and can mobilize their European citizenship to try to escape economic hardship in the host country (Della Puppa and Sredanovic, 2016; McIlwaine and Bunge 2016; Ramos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, research has also shown that the deteriorating economies of receiving states such as Spain have led Andean families to perform onward migration to other European states with better economic conditions such as Belgium (Bermudez and Oso 2018). This contribution situates itself within this particular literature.…”
Section: The Globalized Crisis and Transnational Families' Social Promentioning
confidence: 71%
“…Precarious conditions related to complex interrelations between economic inequalities, social unrest and political violence have long prompted Latin Americans to leave, traditionally for the United States, but more recently for Europe. These flows have been increasingly feminised with women acting as the pioneers with men as husbands, partners and sons following (Bermudez and Oso 2018). Drawing on the empirical data, it emerged that economic precarity underpinned peoples' departure, especially among men (identified by 54 per cent of men and 43 per cent of women in the survey).…”
Section: Feminised Precarious Departures From Latin Americamentioning
confidence: 99%
“…While the crisis affected all migrants, men were especially affected by the collapse of the construction sector with women experiencing more precarious working conditions in their existing jobs (Bermudez and Oso, 2018). Reflecting feminised tropes around gendered expectations, women were more likely to discuss how they made decisions as a way of ensuring the future security of their families and linked with life course factors.…”
Section: Economic Precarity Among Latin Americans Was Widespread On Arrival In Southernmentioning
confidence: 99%
See 1 more Smart Citation